A sub 20 nm metal-conjugated molecule junction acting as a nitrogen dioxide sensor. Issue 14 (27th March 2019) - Wani, Ishtiaq H.; Jafri, S. Hassan M.; Warna, John; Hayat, Aqib; Li, Hu; Shukla, Vivek A.; Orthaber, Andreas; Grigoriev, Anton; Ahuja, Rajeev; Leifer, Klaus
Abstract : A 20 nm gas sensor based on short chain organic molecules detects 55 ppb concentration of NO2 . Abstract : The interaction of a gas molecule with a sensing material causes the highest change in the electronic structure of the latter, when this material consists of only a few atoms. If the sensing material consists of a short, conductive molecule, the sensing action can be furthermore probed by connecting such molecules to nanoelectrodes. Here, we report that NO2 molecules that adhere to 4, 4′-biphenyldithiol (BPDT) bound to Au surfaces lead to a change of the electrical transmission of the BPDT. The related device shows reproducible, stable measurements and is so far the smallest (<20 nm) gas sensor. It demonstrates modulation of charge transport through molecules upon exposure to nitrogen dioxide down to concentrations of 55 ppb. We have evaluated several devices and exposure conditions and obtained a close to linear dependence of the sensor response on the gas concentration.